2003
DOI: 10.1016/j.cub.2003.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Dpp Signaling Silences bam Transcription Directly to Establish Asymmetric Divisions of Germline Stem Cells

Abstract: failure of these proliferating germ cells to differentiate can be recognized by following the fusome since it remains spherical (Figure 1CA) instead of growing into a branched structure [11]. Superficially, therefore, bam mutant cells behaved like GSCs, but molecular markers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
380
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(389 citation statements)
references
References 24 publications
8
380
0
1
Order By: Relevance
“…The BMP signal produced by the somatic cells directly act on GSCs to control their self-renewal and division [17]. It functions as a short-range signal, which is evidenced by the activation of a BMP response gene, Daughters against dpp (Dad), primarily in the GSC [18,[39][40][41], and controls GSC self-renewal by directly repressing the expression of differentiation-promoting genes such as bag of marbles (bam) [18,40]. BMP signaling also has important roles in controlling the division of primordial germ cells (PGCs) in the developing female gonad and the recruitment of GSCs to their niche [42].…”
Section: Genes and Pathways That Control Gsc Self-renewal Proliferatmentioning
confidence: 99%
“…The BMP signal produced by the somatic cells directly act on GSCs to control their self-renewal and division [17]. It functions as a short-range signal, which is evidenced by the activation of a BMP response gene, Daughters against dpp (Dad), primarily in the GSC [18,[39][40][41], and controls GSC self-renewal by directly repressing the expression of differentiation-promoting genes such as bag of marbles (bam) [18,40]. BMP signaling also has important roles in controlling the division of primordial germ cells (PGCs) in the developing female gonad and the recruitment of GSCs to their niche [42].…”
Section: Genes and Pathways That Control Gsc Self-renewal Proliferatmentioning
confidence: 99%
“…We next examined bam-green fluorescent protein (GFP) transgene (a bam promoter fused to the GFP gene; Chen and McKearin, 2003;Kawase et al, 2003) expression. Consistent with earlier reports, we found that bam was expressed in two-to 16-cell spermatogonia but not in GSCs and gonialblasts in the wild-type testis Figure 2 Drosophila BHD homolog (DBHD) regulates male germline stem cell (GSC) maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, extrinsic signals from niche cells help maintain the 'stemness' of the daughter cell still in contact with the niche a member of the bone morphogenetic protein ligand family) signalling are involved. Dpp signalling from cap cells silences bag of marbles (bam) transcription in the stem cell remaining attached to the niche, inhibiting its differentiation [29]. In the Drosophila testis, GSCs and somatic stem cells (SSCs) are also attached to niche (hub) cells, and the hub cells secrete Unpaired (Upd), which ensures self-renewal of both types of stem cell [30].…”
Section: Self-renewal and The Stem Cell Nichementioning
confidence: 99%